In Silico Identification and Functional Impact of Deleterious Nonsynonymous Single-Nucleotide Polymorphisms (nsSNPs) in Type 2 Diabetes–Associated Genes in South Asian Populations - Md. Hafizur Rahman; Md. Numan Islam; Md. Golam Rabby; Salina Shaheen Parul; Md. Mahmudul Hasan; Mrityunjoy Biswas (Genetics Research)
This study explores the impact of nonsynonymous single-nucleotide polymorphisms (nsSNPs) on type 2 diabetes (T2D). The nsSNPs are genetic variations that alter amino acids within proteins, affecting protein structure and function. This study investigated seven candidate genes associated with T2D pathogenesis from genome-wide association studies (GWASs) catalog datasets. Subsequently, six mutation-prediction tools were employed to identify the most harmful nsSNPs within these candidate genes. Further analysis involved evaluating protein evolutionary conservation using the ConSurf server and assessing protein stability with I-Mutant and MUpro. Functional and structural effects were predicted using MutPred2, Project HOPE, and FoldAmyloid tools. We obtained 42 of the most deleterious nsSNPs from identified candidate genes. Among these, 38 are located in highly conserved residues with a conservative score of 7–9. Furthermore, 20 of these conserved nsSNPs are found to decrease protein stability, with 18 of them classified as pathogenic mutations. These mutations can either reduce or increase protein size and can alter the charge and hydrophobic characteristics of the affected proteins. In addition, eight mutants from four genes were identified in amyloidogenic regions, suggesting a potential link to protein aggregation. These findings provide valuable insights into the physicochemical properties and structural changes associated with these deleterious nsSNPs. The study concludes that the distinctive physicochemical properties and significant structural changes of the identified nsSNPs suggest valuable insights for future research. Understanding these variants through large-scale studies may pave the way for developing therapeutic interventions targeting genetic variations, ultimately improving our understanding of T2D pathogenesis and treatment.